English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-02-04 12:59:57 · 5 answers · asked by nett09621 1 in Science & Mathematics Mathematics

5 answers

6+y=5
y=-1

2007-02-04 13:02:48 · answer #1 · answered by Sharp Marble 6 · 1 0

Replace x with 2:
3(2)+y=5
6+y=5
y=-1

Check:
2=2

3(2)-1=5
6-1=5
5=5

2007-02-04 21:03:39 · answer #2 · answered by Anonymous · 0 0

if x=2 than I would say um replace X with 2 in the equation than it would look like 3(2)+y=5 so 3 times 2 is 6 soo you come up with 6+y=5 sub 5 on both side soo you can find what y is equal to the answer is y= -1

2007-02-04 21:08:47 · answer #3 · answered by Ms`z Diamond 1 · 0 0

If you are finding the value of y here is the answer.


since the value of x is 2 then substitute x to 3x+y=5

3(2)+y=5
6+y=5
y=5-6
y=-1

2007-02-04 21:05:19 · answer #4 · answered by Elmer 2 · 0 0

y= -1

2007-02-04 21:07:49 · answer #5 · answered by unrestedmind 2 · 0 0

fedest.com, questions and answers